THE SOCIO-RACIAL DEVELOPMENT OF BLACK WOMEN IN THE FACE OF INTERSECTIONALITY OF IDENTITIES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article aims to address the stories, struggles, achievements and challenges in the development of black women in Brazilian society, in the face of their intersectionality and the confrontation with racism, machismo, sexism and patriarchy. This is a bibliographic research combined with data and statistics research, for this reason, the methodology applied will be qualitative and quantitative. Intersectional Theory concerns the study of overlapping social identities and correlated systems of oppression, domination and/or discrimination. The intersectionality between oppressed social groups of gender and race, when they intersect, gives rise to different realities, issues and problems. For this reason, within a feminist movement, the agendas of black women must be treated in a unique way, as they are different from the agendas of white, indigenous and foreign women. In Brazil, feminist women have as their main objective to resist the sexist and patriarchal system of communities throughout the country, while seeking their rightful spaces. However, it must be considered that the historical context of the country presents a plurality of women, so there is, therefore, a plurality of issues from various sectors (economics, political, social, legal) and this article is justified by evaluating all this reality in a theoretical and practical way. Therefore, the expected results show the undoubted socio-racial inequality present in the life of black Brazilian women, deconstructing theoretical references such as the Theory of Racial Democracy and the hypersexualization of these bodies, in the search for the recognition of their humanity and identity.